Learning and practice of innovation in the university: actors, spaces and communities - González-Nieto, Noé Abraham; Fernández-Cárdenas, Juan Manuel; Reynaga-Peña, Cristina G. (IE Revista de Investigación Educativa de la REDIECH, 2019)
Universities have started a process to transform their physical spaces in places where innovation is practiced, promoted and built. This study presents an analysis of the data obtained in an innovation laboratory of a university in northern Mexico, where students, professors and collaborators (actors) participate in interdisciplinary projects to put innovation into practice. Through a qualitative methodology with a focus on grounded theory and with the use of interviews and focus groups, categories are established based on the functions, uses, and identities that this space provides for its users, as well as the challenges of innovation in the academic context. The results indicate that in the context studied, the sense of belonging, collaborative learning and networking are fundamental criteria for creating an innovation ecosystem. Also, we emphasize the importance of having innovation spaces within the university to transform the teaching and learning experiences of students and teachers alike.